Potensi Klaster Agroindustri Usaha Mikro Kecil dan Menengah di Provinsi Jambi - Junaidi Junaidi; Amri Amir; Hardiani Hardiani (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2014)
The purpose of research is to 1). Analyzing the agro-industry group of SMEs that have the potential to be developed as an agro-industry clusters of SMEs in Jambi Province; (2. Analyze the various potentials, opportunities, barriers and challenges in the development of agro-industry SMEs in Jambi Province. The data used consist of primary data and secondary data. Primary data were collected from experts and stakeholders associated with agro-industry and agro-industry businesses. Collecting data using a structured questionnaire and interview. Secondary data sourced from related institutions / organizations at the national, provincial, district and sub-district. To identify and analyze the potential for agro-industry SME cluster development is done with consideration of the number of business units and discussions with the experts to get the cluster potential agro-industry group. Furthermore, to analyze the potential, opportunities, barriers and challenges of development of agro-industry cluster analyzed descriptively based on surveys and direct observation in the agro-industry businesses that have the potential clusters in Jambi Province. . The analysis was done by descriptive against internal and external conditions of SMEs. The results found that there are five groups of agroindustrial SMEs that have the potential to be developed in clusters, namely: industrial tempe / tofu soy: copra industry; industrial crackers, chips, dent and the like; industrial woven from rattan and bamboo instead of wood furniture as well as industry. Furthermore, in terms of business development, SMEs in Jambi Province showed relatively good progress, especially when seen from the development of production volume, revenue / turnover, product selling prices, raw material prices and profits. However, there are major obstacles in the development of the agro-industry is the future of SMEs, especially those related to the availability of raw materials, labor, market share and production equipment. Keywords: cluster,agro-indsutry,business development